2022
DOI: 10.3892/mmr.2022.12690
|View full text |Cite
|
Sign up to set email alerts
|

HOXB2 increases the proliferation and invasiveness of colon cancer cells through the upregulation of CCT6A

Abstract: colon cancer has a high mortality rate, thus there is an urgent need to develop novel therapeutic options for clinical management of the disease. Studies have revealed that chaperonin containing TcP1 subunit 6a (ccT6a) promoted the development of multiple types of cancer, and dataset analysis revealed that homeobox B2 (HoXB2) has the potential to modulate the expression of ccT6a. However, whether HoXB2 affects the proliferation, migration and invasion of colon cancer cells remains to be determined. a ccT6a kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The present study also revealed that increased tumor CCT6A expression was associated with higher Enneking stage (IIB vs. IIA) and abnormal serum LDH (vs. normal), whereas elevated tumor CDC20 expression was associated with higher Enneking stage in patients with osteosarcoma. The probable reasons for this may be: i) Increased tumor CCT6A and CDC20 expression could facilitate the extra-periosteal invasion of tumor cells; therefore, increased tumor CCT6A and CDC20 are linked with increased Enneking stage in patients with osteosarcoma ( 11 , 33 ); and ii) elevated tumor CCT6A could promote tumor cell migration ( 11 ); thus, an increase in tumor CCT6A is associated with abnormal serum LDH in osteosarcoma patients. Therefore, increased tumor CCT6A and CDC20 expression may be associated with a worse tumor burden in patients with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also revealed that increased tumor CCT6A expression was associated with higher Enneking stage (IIB vs. IIA) and abnormal serum LDH (vs. normal), whereas elevated tumor CDC20 expression was associated with higher Enneking stage in patients with osteosarcoma. The probable reasons for this may be: i) Increased tumor CCT6A and CDC20 expression could facilitate the extra-periosteal invasion of tumor cells; therefore, increased tumor CCT6A and CDC20 are linked with increased Enneking stage in patients with osteosarcoma ( 11 , 33 ); and ii) elevated tumor CCT6A could promote tumor cell migration ( 11 ); thus, an increase in tumor CCT6A is associated with abnormal serum LDH in osteosarcoma patients. Therefore, increased tumor CCT6A and CDC20 expression may be associated with a worse tumor burden in patients with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperonin-containing tailless complex polypeptide 1 subunit 6A (CCT6A) is a recently discovered oncogene, which promotes cancer progression by facilitating the proliferation, invasiveness and stemness and of tumor cells (10)(11)(12)(13). In addition, it exhibits potency as a prognostic marker in numerous types of cancer, such as lung cancer, gastric cancer and papillary thyroid carcinoma (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, it was noticed that CCT6A protein expression was upregulated in tumor tissue compared with non‐tumor tissue in PTC patients, which could be explained as that: CCT6A promoted cell proliferation, invasion, and malignant behaviors in PTC, which were the hallmarks of cancer, thus an increase of CCT6A in tumor tissue from PTC patients was observed. 5 , 6 , 7 , 21 Moreover, higher CCT6A expression was related to extrathyroidal invasion and advanced pathological stages in PTC patients, which could be explained as that CCT6A activated the transforming growth factor (TGF)‐β signaling pathway to promote PTC cell proliferation and cell invasion, thus led to a positive correlation of tumor invasion as well as advanced pT and pTNM stage in PTC patients. 6 , 22 Notably, it was also discovered that tumor CCT6A high could serve as an independent factor for reduced DFS and OS in PTC patients, indicating its potential prognostic values in PTC management.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperonin‐containing tailless complex polypeptide 1 subunit 6A (CCT6A) is reported to be closely involved in the pathogenesis of hepatocellular carcinoma (HCC), non‐small‐cell lung carcinoma (NSCLC), and colon carcinoma; also CCT6A has been identified as one potential prognostic biomarker of carcinoma in the clinical filed. 5 , 6 , 7 , 8 , 9 , 10 , 11 Moreover, CCT6A is also reported to interact with various oncoproteins to participate in carcinoma development and progression. For instance, CCT6A interacts with the cell division cycle protein 20 (CDC20) during prometaphase in HeLa cells; CDC20 also interacts with cyclin B1 (CCNB1) and polo‐like kinase 1 (PLK1); PLK1 is linked with CCNB1 in HCC cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation